Characterization of Polymer Assisted Nano Silver by Chemical Reduction Method - Punitha1, N.; Ramesh2, P.S. (Asian Journal of Chemistry, 2013)
Silver nano particles were simply synthesized by chemical reduction method. Silver nitrate is used as a base material and polyethylene glycol, chitosan, polyethylene oxide and polymethyl methacrylate were used as stabilizers along with sodium citrate as reducing agent. The well organized silver nano particles in polymers were obtained at certain concentration ratio of polymers to silver nitrate at temperature below its decomposition (300 ºC). At all other concentrations the silver particles were polydispersed due to imperfect confinement. The SEM pictures reveal that the different stabilizers give rise to different shapes which vary from spherical to wire like to flaky ones. The biodegradable chitosan polymer seems to have more size control capacity than the other synthetic polymers.